Sistem Pendeteksi Bencana Kebakaran Menggunakan ESP32 Dan Arduino Berbasis WEB: Studi Kasus Di Toko Citra Berkah Karangawen Demak - Muhammad Ainun Najib; Sulartopo Sulartopo; Dani Sasmoko; Danang Danang; Iman Saufik Suasana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Fire is a threat to human safety, property and the environment. With the increasingly rapid development and progress of development, the risk of fires is increasing. Shophouses or shophouses are places that are prone to fires. The increasingly dense population and the construction of office buildings have created a vulnerability in the event of a fire. Preventive efforts must be carried out by each individual and work unit, so that casualties from fire incidents can be minimized. Fires can cause moral, material and even human life losses. Fires that hit public facilities, of course, cause losses to many people. Shophouse fires often occur suddenly due to short circuits, gas explosions or due to sparks from cigarettes/matches. The research carried out this time focuses on creating a fire detection system using ESP32 and Arduino. The system uses three sensors, namely a temperature sensor, a gas sensor and a fire sensor. Temperature sensors are useful for monitoring room temperature conditions, fire sensors are useful for detecting the presence of fire in a fire disaster and gas sensors are useful for detecting the presence of smoke that appears as a result of a fire disaster. This system uses an ESP32 microcontroller and uses the Arduino IDE application. The results of the fire detection system are expected to reduce the occurrence of fire accidents and also losses caused by fire accidents.